CUSTOMER SATISFACTION ANALYSIS “FEEDER WIRAWIRI SUROBOYO” PARK AND RIDE ROUTE MAYJEND SUNGKONO–CITY HALL USING CSI AND IPA METHODS - Nachika Kusuma Wardany; Kurnia Hadi Putra; Theresia Maria Chandra Agusdini (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2024)
Surabaya, as one of the big cities in Indonesia, experiences significant challenges in transportation due to rapid growth of infrastructure and population. One of the government's efforts to overcome this problem is by launching Feeder Wirawiri Suroboyo, an integrated public transportation service that supports mass transportation modes in Surabaya. This study aims to analyze the characteristics and level of customer satisfaction using the Customer Satisfaction Index (Satisfaction) and Importance Performance Analysis (Importance) methods. The results of the analysis obtained the characteristics of the average passenger is male, aged <17 years and 18-28 years with a last education of high school or equivalent who are students with income <Rp. 2,000,000 who use Feeder Wirawiri Suroboyo Park and Ride route Mayjend Sungkono-City Hall with the purpose of traveling for School/College.The satisfaction level is 93.78%, which means it is included in the very satisfied category, while the suitability level is 95.68%, which is then calculated as the average score of the suitability level to be analyzed using the Cartesian Diagram. Keywords: Wirawiri Suroboyo Feeder; Customer Statistics Index; Importance Performance Analysis.